PATRIOTISM BETWEEN NATIONAL IDENTITY OF PEOPLE AND NEOLIBERALISM - Djordjevic, Radomir D; Kostadinović, Andon (Journal of process management and new technologies, 2020)
The paper deals with the problem of patriotism as a national identity of peoples and neoliberalism, as increasingly present in developing countries as well as in other countries. Today's meaning of patriotism has largely darkened everyone's struggle against everyone, especially the world market. The emergence of multinational companies and the increasing presence of the imposition of certain conditions in many countries - in political, military, social, economic and every other spheres is more and more present.The authors in theory view this situation in our country as well, and then globally. They consider that patriotism, as an internal state or consciousness of a nation about itself, has been greatly altered in favor of so-called neoliberal capitalism, which enters into every country that permits it, or vice versa - by force of imposes different behavior.           Neoliberalism is an old-fashioned approach to expressing a society that is trying to transfer its free-market behavior to other countries, thus transforming one country or transforming it into a different-type colony with the help of the domestic political elite.
Keywords: patriotism, neoliberalism, peoples identity, liberalism, world market, globalism.